MANAJEMEN PENDIDIKAN KARAKTER DI UNIVERSITAS PANCASAKTI (UPS) TEGAL - Mr. Basukiyatno; Mr. Budiyono; Beni Habibi (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2016)
This study attempts to mendiskripsikan management character education at the university of pancasakti tegal. This research adopting descriptive-qualitative namely research that only describes the phenomena of subject research in they are, by exposure to the results of the study qualitatively. Informants as a source of data were chosen purposively, that is set in the a person who is regarded know a lot about problems the treatment. This informant covering officials, lecturers teaching MPK, and students in a limited number of. The result of research give a description, that in oops tegal character education carried out by of several units of institutions, among others. (1) management unit matakuliah develop the character of (MPK), (2) units for student activities, (3) a unit spirituality. Concluded that third implementation unit character education has yet to walk by satisfactory. The findings from the field indicated distortion, deficiency, obstacles and overlapping management in character education. MPK can’t run optimal, both in terms of management, lecturers, management learning, and evaluation. Activities kemahasiswaan had a role good for participants , honey do not all students come in it , unit spirituality is not widely known and interested in. The implications of the result of this research is character education in oops will participate and function optimally, when university pancasakti tegal could compatibly combine three implementation unit character education so the all parties concerned can optimize the role of each others. Keywords: management , character education , student activities.